Advances in drug delivery to the posterior segment. Issue 3 (May 2015) - Pearce, William; Hsu, Jason; Yeh, Steven
<x xml:space="preserve">Abstract</x> Purpose of review Emerging developments and research for drug delivery to the posterior segment offer a promising future for the treatment of vitreoretinal disease. As new technologies enter the market, clinicians should be aware of new indications and ongoing clinical trials. Recent findings This review summarizes the advantages and shortcomings of the most commonly used drug delivery methods, including vitreous dynamics, physician sustainability and patient preferences. Currently available, intravitreal, corticosteroid-release devices offer surgical and in-office management of retinal vascular disease and posterior uveitis. The suprachoroidal space offers a new anatomic location for the delivery of lower dose medications directly to the target tissue. Implantable drug reservoirs would potentially allow for less frequent intravitreal injections reducing treatment burdens and associated risks. Newer innovations in encapsulated cell technology offer promising results in early clinical trials. Summary Although pars plana intravitreal injection remains the mainstay of therapy for many vitreoretinal diseases, targeted delivery and implantable eluting devices are rapidly demonstrating safety and efficacy. These therapeutic modalities offer promising options for the vitreoretinal therapeutic landscape.